Applying the neuroscience of creativity to creativity training - Onarheim, Balder; Friis-Olivarius, Morten (Frontiers in Human Neuroscience, 2013)
This article investigates how neuroscience in general, and neuroscience of creativity in particular, can be used in teaching 'applied creativity' and the usefulness of this approach to creativity training. The article is based on empirical data and our experiences from the Applied NeuroCreativity (ANC) program, taught at business schools in Denmark and Canada. In line with previous studies of successful creativity training programs the ANC participants are first introduced to cognitive concepts of creativity, before applying these concepts to a relevant real world creative problem. The novelty in the ANC program is that the conceptualization of creativity is built on neuroscience, and a crucial aspect of the course is giving the students a thorough understanding of the neuroscience of creativity. Previous studies have reported that the conceptualization of creativity used in such training is of major importance for the success of the training, and we believe that the neuroscience of creativity offers a novel conceptualization for creativity training. Here we present two sets of empirical data, suggesting that principles from neuroscience can contribute effectively to creativity training and produce measurable results on creativity tests: 1) an experiment demonstrating how an ANC lecture on the neurobiology of creativity significantly decreased the number of fixations in a creative task, 2) pre/post-training tests showing that ANC students gained more fluency in divergent thinking (a traditional measure of trait creativity) than those in highly similar courses without the neuroscience component. The evidence presented indicates that the inclusion of neuroscience principles in a creativity course can in 8 weeks increase divergent thinking skills with an individual relative average of 28.5%.